Measurement and Control of the Inside Greenhouse Climate Using Neural Network Prediction and Fuzzy Logic Controller - Lalmi D. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
To change the environment in which plants thrive, protected agriculture employs a variety of techniques. In a perfect world, plant growth would happen in climate-optimal locations with no need for protective structures. This is not the case, though, as the majority of nations mandate various types of agriculture in controlled environments to save crops from climatic and environmental extremes. High sun radiation is available in arid areas, but they also have challenging relative humidity and temperature ranges. This study’s goal is to evaluate the effectiveness of a cooling system installed in an agricultural greenhouse for a semi-arid environment. The design of two greenhouses—one with and one without a cooling system—is the main topic of the work. The experimental greenhouse (with a cooling system) has cooler temperatures than the control greenhouse. While the humidity is higher than in the control greenhouse, the temperatures are lower in the experimental greenhouse (with cooling system).These results demonstrate the system’s dependability in this region, which offers significant solar radiation but also challenging conditions for temperature and relative humidity.